Potential Impacts of Agritourism in South Miami-Dade County - Edward Evans; Alan Hodges (EDIS)
As the impacts of trade liberalization and globalization continue to unfold, many agricultural producers are finding it extremely difficult to sustain their current levels of profits, let alone increase profit margins. Caught in a price-cost squeeze situation, with declining or stagnating prices concomitant with rising input costs, agricultural producers are looking for alternatives to replace or supplement traditional farm operations, hoping to reverse the steady erosion in net farm income. One increasingly popular alternative in some areas of the United States is agritourism. This is EDIS document FE637, a publication of the Food and Resource Economics Department, UF/IFAS Extension. Published May 2006.